Development, validation and evaluation of a rapid PCR-nucleic acid lateral flow immuno-assay for the detection of Plasmodium and the differentiation between Plasmodium falciparum and Plasmodium vivax. - Mens, P; Moers, A; de Bes, L; Flint, J; Sak, JR; Keereecharoen, L; van Overmeir, C; Verweij, J; Hallett, R; Wihokhoen, B; Proux, S; Schallig, H; et al. (BioMed Central, 2012)
BACKGROUND: Molecular tools are very sensitive and specific and could be an alternative for the diagnosis of malaria. The complexity and need for expensive equipment may hamper implementation and, therefore, simplifications to current protocols are warranted. METHODS: A PCR detecting the different Plasmodium species and differentiating between Plasmodium falciparum and Plasmodium vivax was developed and combined with a nucleic acid lateral flow immuno-assay (PCR-NALFIA) for amplicon detection. The assay was thoroughly evaluated for the analytical sensitivity and specificity in the laboratory, the robustness and reproducibility in a ring trial and accuracy and predictive value in a field trial. RESULTS: The analytical sensitivity and specificity were 0.978 (95% CI: 0.932-0.994) and 0.980 (95% CI: 0.924-0.997), respectively, and were slightly less sensitive for the detection of P. vivax than for P. falciparum. The reproducibility tested in three laboratories was very good (k = 0.83). This evaluation showed that the PCR machine used could influence the results. Accuracy was evaluated in Thailand and compared to expert microscopy and rapid diagnostic tests (RDTs). The overall and P. falciparum-specific sensitivity and specificity was good ranging from 0.86-1 and 0.95-0.98 respectively, compared to microscopy. Plasmodium vivax detection was better than the sensitivity of RDT, but slightly less than microscopy performed in this study. CONCLUSION: PCR-NALFIA is a sensitive, specific and robust assay able to identify Plasmodium species with good accuracy. Extensive testing including a ring trial can identify possible bottlenecks before implementation and is therefore essential to perform in additon to other evaluations.